2006
DOI: 10.1002/mrd.20509
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclases in oocyte maturation: A characterization of AC isoforms in bovine cumulus cells

Abstract: Mammalian oocytes are arrested at the G(2)/M transition in the meiotic cell cycle. It is well known that a decrease in intraoocyte cAMP concentrations accompanies resumption of meiosis, but the precise trigger of this decrease remains a mystery. Follicular somatic cells are intimately coupled to the oocyte and are thought to transmit maturation signals to the oocyte in response to hormonal stimulation. Here, we investigate the nature of the follicular somatic cell response to hormonal stimulation by identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…LH‐induced Ca 2+ rises are biphasic as a result of the cumulative contribution of Ca 2+ influx and intracellular Ca 2+ mobilization (Davis et al, 1987; Alila et al, 1989; Mattioli et al, 1990) (unpublished data). Studies in bovine COCs demonstrated that the LH‐induced [Ca 2+ ] i rise causes [cAMP] i elevation in cumulus cells by activating Ca 2+ ‐sensitive adenylate cyclases; in particular, the activity of adenylate cyclase I seems to be stimulated by [Ca 2+ ] i rises resulting from Ca 2+ influx (Lastro et al, 2006). In rodent oocytes, on the other hand, Ca 2+ is able to inactivate all the three adenylyl cyclases identified, and this leads to a drop of [cAMP] i (Hanoune and Defer, 2001; Wang and Storm, 2003).…”
Section: Does a [Ca2+]i Rise Participate In The Onset Of Oocyte Maturmentioning
confidence: 99%
“…LH‐induced Ca 2+ rises are biphasic as a result of the cumulative contribution of Ca 2+ influx and intracellular Ca 2+ mobilization (Davis et al, 1987; Alila et al, 1989; Mattioli et al, 1990) (unpublished data). Studies in bovine COCs demonstrated that the LH‐induced [Ca 2+ ] i rise causes [cAMP] i elevation in cumulus cells by activating Ca 2+ ‐sensitive adenylate cyclases; in particular, the activity of adenylate cyclase I seems to be stimulated by [Ca 2+ ] i rises resulting from Ca 2+ influx (Lastro et al, 2006). In rodent oocytes, on the other hand, Ca 2+ is able to inactivate all the three adenylyl cyclases identified, and this leads to a drop of [cAMP] i (Hanoune and Defer, 2001; Wang and Storm, 2003).…”
Section: Does a [Ca2+]i Rise Participate In The Onset Of Oocyte Maturmentioning
confidence: 99%
“…These differences between species are likely to be related to differences in adenylate cyclase and PDE activity within the oocyte. In most species, exposure to gonadotrophins or forskolin increases production of cAMP within the cumulus cells, which activates type II protein kinase A (PKA) and stimulates cumulus expansion (Bornslaeger and Schultz 1985;Downs and Hunzicker-Dunn 1995;Thomas et al 2002;Lastro et al 2006). Increased cAMP production and activation of type II PKA within the cumulus cells can also lead to the resumption of meiosis, but this stimulatory effect is dependent on the concentration of cAMP and the associated activity of type I PKA within the oocyte (Downs and Hunzicker-Dunn 1995).…”
Section: Reversible Meiotic Arrest In Feline Oocytesmentioning
confidence: 99%
“…It may be that oocytes are highly sensitive to cAMP and even small changes in intracellular concentrations of cAMP that are not statistically significant can have biologically significant effects on the oocyte. Detecting these subtle differences may be further complicated by the large variability in COC quality and cAMP content when oocytes or cumulus cells are recovered from follicles at different stages of maturation (Lastro et al 2006;Bagg et al 2009;Sasseville et al 2009). Finally, it is necessary to maintain cAMP concentrations within the oocyte during sample collection and processing before the assay.…”
Section: Reversible Meiotic Arrest In Feline Oocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results indicate that bovine oocytes and cumulus cells may contain AC isoforms with different sensitivities to Mn 2+ . Lastro et al, (2006) determined that bovine cumulus cells obtained from follicles 2-8 mm contained mRNA for AC isoforms 1, 3, 4, 6, and 9 and were enriched in PKC-inhibited isoforms 4 and 6 and the Ca 2+ -stimulated isoform 1. However, the AC isoforms of bovine oocytes have not yet been determined.…”
Section: Role Of Camp In the Control Of Bovine Oocyte Meiosismentioning
confidence: 99%